State abandonment and the resurgence of Indonesian Islamic State (NII) movements - Rifai, Akhmad; Putra, Kristian Adi; Rifai, Ainrisq Auliya; Izudin, Ahmad; Septiani, Evi (Indonesian Journal of Islam and Muslim Societies, 2025)
This article aims to investigate the reasons contributing to the emergence of the Indonesian Islamic State (NII) in Garut Regency, particularly in the context of state regulations that prohibit movements advocating for Islamic revivalism. Employing a case study approach, data were collected through observation, interviews, and documentation over a four-month period (September–December 2022), leading to several significant findings. The initial discovery elucidated a covert recruitment strategy that leveraged a network of pesantrens and religious leaders, employing deceptive identities to evade detection. The second result highlighted the ability of the NII to persist in the face of state prohibitions by capitalizing on regulatory loopholes and the inadequate coordination between central and regional government entities. The third finding investigated the influence of structural poverty and inadequately targeted development initiatives as significant factors driving community engagement in the revivalist movement, leading to the NII’s public declaration of its presence. These phenomena underscore the state’s ongoing negligence and disregard, ostensibly under the guise of promoting openness and freedom of expression in a democratic context, which seemingly facilitates the existence of Islamic revivalist groups. This situation is further exploited by politicians within a bureaucratic plutocracy, particularly during election campaigns, to garner support from potential voters. Tulisan ini berusaha menggali alasan di balik kebangkitan Negara Islam Indonesia (NII) di Kabupaten Garut, dan mengapa hal ini muncul di tengah aturan negara yang melarang gerakan Islamic revivalism. Dengan pendekatan studi kasus dan pengumpulan data melalui observasi, wawancara, dan dokumentasi selama empat bulan (September–Desember 2022), ditemukan beberapa temuan kunci. Temuan pertama berhasil mengungkap strategi rekrutmen tersembunyi yang memanfaatkan jaringan pesantren dan tokoh agama dan penggunaan identitas kamuflase untuk menghindari deteksi. Temuan kedua mengungkap keberhasilan NII eksis di tengah pelarangan negara dengan cara memanfaatkan celah regulasi dan koordinasi yang lemah antara pemerintah pusat dan daerah. Temuan ketiga mengkaji peran kemiskinan struktural dan program pembinaan yang tidak tepat sasaran sebagai faktor pendorong keterlibatan masyarakat dalam gerakan revivalis sehingga NII ini secara terang-terangan mendeklarasi diri di hadapan publik. Fakta-fakta ini menunjukkan kelalaian dan pengabaian negara yang terus berlanjut dengan dalih keterbukaan dan kebebasan berpendapat di era demokrasi, seolah memberikan ruang bagi kelompok revivalis Islam untuk tetap eksis, dimanfaatkan oleh politikus dalam agenda plutokrasi birokrasi dan momentum kampanye pemilu guna meraih simpati konstituen potensial